Веб-система для розповсюдження результатів мистецької діяльності - Драконова, О. О. (ХНУРЕ, 2024)
This work is devoted to the development of a web application to create an environment for the dissemination of cultural reality, which will consist of server and client applications. As part of this work, an algorithm for optimizing images will be developed, since they are an integral part of this project. To do this, we will reduce the size, weight and expansion of images added to the web resource. The resulting result will contain minimally resource-intensive images.
Keywords: веб-система; мистецька діяльність